The Personhood of the Dead: Morality, Memory, and Posthumous Dignity - UDISI , Ebikisei Stanley (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2025)
The research highlights the central role of memory in shaping societal attitudes toward the deceased, drawing on philosophical, legal, and sociological perspectives to analyze how collective memory transcends individual existence. It argues that while the dead lack conscious existence and cannot experience harm or dignity, their memory and legacy impose moral and ethical obligations on the living. The injunction De mortuis nil nisi bonum (“Speak no ill of the dead”) reflects the societal desire to preserve the dignity and reputation of the deceased, even as it raises questions about censorship, freedom of expression, and the accurate representation of history. Ultimately, this study concludes that the concept of posthumous rights is less about the dead themselves and more about how the living choose to honor, remember, and engage with the past. It calls for a nuanced balance between respecting the dignity of the dead and upholding the freedoms of the living, offering fresh insights into the evolving relationship between memory, morality, and law. By addressing these timeless questions, the research contributes to ongoing debates about personhood, rights, and the ethical responsibilities that transcend the boundaries of life and death.